STRUKTUR VOLATILITAS PENDEKATAN GARCH DAN TARCH - Kamaludin , (Media Riset Bisnis & Manajemen, 2008)
Reversal of direction of the securities price is quickly causes hish volatility and difficult to predict. Sometimes direction of volatility to return is not only correlation become negatively, but has the symmetric relationship. So anomaly return of security is not necessary followed by volatility on the same day. This research tries to know the volatility structure in market ASIAN. Approach of analysis used is GARCH and TARC methose Result of this research indicates that there is strong correlation between volatility situations and situation return. But situation of volatility doesn't have the symmetric relationship with situation return on that week.Keyword: Retu4n, Volatility GARCH and TARCH, Security price